Formulation of repellant gel of vetiver oil : Composition of carbopol 3% w/v – propilenglicol optimization - Sri Hartati Yuliani (Indonesian Journal of Pharmacy, 2005)
3% w/v solution and propilenglikol,and to observe the dominant effect among Carbopol 3% w/v, propilenglikol and their interaction in determining the physical properties of vetiver oil repellant gel. Moreover the repellant potency against female Aedes albopictus and iritation skin test on rabbit were also confirmed.Firstly, vetiver oil was collected from dried root of Vetivera zizoioides (L) Nogh by water steam destilation. The obtained oil then was gelled by the aid of Carbopol 3% w/v solution – propilenglikol at various compositions. Factorial design method was employed to create the optimum composition of Carbopol 3% w/v solution – propilenglikol and was used to determined the effect of Carbopol 3% w/v solution – propilenglikol and their interaction on the gel characteristics.The result showed that the effect of Carbopol 3% w/v solution was the dominant factor in the viscosity and repellant potency. While the effect of propilenglikol was the dominant factor in alteration of gel viscosity. The interaction between Carbopol 3% w/v solution and propilenglikol was dominant factor in spreadability. The optimum composition was created in superimposed countour plot. Irritation skin test on rabbit confirmed that all evaluated formulas were non irritatingKey words: formulation, repellant gel, vetiver oil